Analyzing Kids Responses Towards TV Commercials (Case Study: Spongebob of Global TV) - Riskyananda, Laras; Hudrasyah, Herry (Journal of Business and Management, 2015)
Abstract Ã¢â‚¬â€œ Most marketers say that television advertising has become less effective in the past two years, but many are interested in exploring new ad formats and forms of video commercials, according to the Association of National Advertisers and Forrester Research in 2008. Therefore, existence of advertising on children's TV show is still questionable whether good or bad impact generally. The objectives of this research is to to identify the capablities of the children in understanding brand in TV commercial, to analyze the capabilities of the children in remembering the commercials, to identify the influence of TV commercial on kids TV show to a child desire in watching that show, and to identify the influence of TV commercial on kids TV show to purchase intention.Ã‚Â Keywords Ã¢â‚¬â€œ Kids responses, TV commercials, consumption behavior, psychology of perceptions, purchase intention